Plant-Derived Antioxidants Protect the Nervous System From Aging by Inhibiting Oxidative Stress - Cui, Xiaoji; Lin, Qinlu; Liang, Ying (Frontiers in Aging Neuroscience, 2020)
Alzheimer's disease (AD) has become a major contributing disease to human death and thought to be closely related to the aging process. The rich antioxidant substances in plants have been shown to play a role in delaying aging and in recent years significant research has been focused on also examining their potential role in AD onset and progression. Many plant-derived antioxidants research studies have provided insights for the future treatment and prevention of AD. This article reviews various types of plant-derived antioxidants with anti-aging effects on neurons. This article distinguishes the different types of active substances that exhibit different degrees of protection for the nervous system and summarizes the mechanisms thereof. Plant-derived antioxidants with neuroprotective functions can protect various components of the nervous system in a variety of ways and can have a positive impact on interventions to prevent and alleviate AD. Furthermore, when considering neuroprotective agents, glial cells also contribute to the defence of the nervous system and should not be ignored.